(untitled) (Economics and region, 2017)
UDC 338:336.02:621.311 Svitlana Sivitska, Ph.D., Associate Professor at Finance and Banking Department, Vice-Rector for Scientific, Educational, Social Work and International Cooperation. Poltava National Technical Yuri Kondratyuk University. Identification of strategic priorities of investment into development of alternative energetics. There are the stages of the methodology for choosing the strategic priorities of investing in alternative energy explored in the article. The potential of alternative energy analyzed. The strategic priorities of alternative energy have been explored. An integrated analysis of the potential of alternative energy is carried out on the territorial basis done. The matrix of choice of strategic priorities of investing in alternative energy determined. Keywords: energetic security, alternative energetics, renewable sources of energy, investment, strategic priorities, matrix.